Inflation, Monetary Policy, and Systemic Risks: Global Insights from the Post-Crisis Era - Setiadi (Indonesian Scientific Publication, 2025)
The dynamics of inflation and monetary policy between 2008 and 2025 have been shaped by unprecedented global crises, including the financial crisis, the COVID-19 pandemic, and recurrent energy and commodity shocks. This study aims to synthesize global lessons on how inflation evolves under these conditions and how central banks have responded with both conventional and unconventional policies. The methodology employed a structured narrative review, drawing from Scopus, Google Scholar, Web of Science, JSTOR, and complementary databases. Keywords such as “inflation dynamics,” “monetary policy,” “COVID-19,” “supply shock,” and “economic recovery” guided the search. Inclusion criteria focused on peer-reviewed studies addressing the intersection of inflation and policy during the designated period. The results highlight four key themes. First, external shocks such as energy and food price volatility strongly influence inflation, with greater vulnerability observed in open economies. Second, monetary policy effectiveness varies: advanced economies relied on interest rate adjustments and unconventional tools, while developing economies faced structural limits in transmission. Third, fiscal-monetary coordination enhanced stability, whereas uncoordinated responses fueled uncertainty and inflationary persistence. Finally, public attention and expectations significantly shaped inflation outcomes, limiting the scope of communication strategies. The discussion situates these findings within broader systemic factors including globalization, market structures, and geopolitical risks, underscoring the need for adaptive and credible policy frameworks. This study concludes that future resilience requires strengthening central bank independence, improving coordination, and integrating global risk analysis. Such measures are critical for sustaining price stability in an era of persistent global volatility.